Behavioral Finance In Decision Making: An Experimental Study Of Investor Bias And Indonesian Private Market Anomalies - Abdul Rosid; Isabella, Astrid Aprica; Hartoto, Hartoto; Siswantini, Tri; Suharyati, Suharyati (SEAN Institute, 2024)
This research aims to identify the influence of cognitive bias on investment decisions in the Indonesian capital market, with a focus on overconfidence, herd behavior and loss aversion. Using an experimental approach, 100 individual investors participated in an investment simulation to test related hypotheses. Data was collected through questionnaires and observations during the simulation, analyzed using linear regression and ANOVA. The results show that overconfidence increases transaction frequency and risk, herd behavior causes behavior to follow the majority which triggers market volatility, and loss aversion causes investors to hold losing stocks for too long and quickly sell profitable stocks. These findings provide important insights for investment managers and market regulators to design strategies that reduce the negative impact of cognitive biases and improve market stability and performance.